(untitled) (Regional aspects of productive forces development of Ukraine, 2019)
The article is devoted to the planning of business career and professional training of personnel. It is noted, in particular, that the most important problem of forming personnel potential of employees is their career growth and training. The article emphasizes that the priority tasks of increasing the efficiency of the operation of enterprises is to equip them with workers who have the necessary qualities to successfully own a chosen profession, to create a system that allows them to maintain and develop their working capacity, as well as reliability. To perform such tasks, periodic control of the employee’s functional status and the definition of objective criteria characterizing the qualitative composition of such units and bodies are necessary. The peculiarities of career growth and professional training of the personnel are investigated. The efficiency of the existing system at the enterprise level is analyzed. The authors noted that the key to a successful career is a symbiosis of such factors as the employee’s inner desire to grow professionally, hard work and charisma. It is also emphasized that personnel training plays an important role. Advanced advanced countries of the world have long been exploring the impact of training on human productivity. Consequently, one of the strategic goals of modern Ukrainian firms and organizations should be to train managers to develop their own development and manage the development of their subordinates in the most effective way. For this purpose it is necessary to create a system of career growth, training of managers of all levels.